DOPA-based paclitaxel-loaded liposomes with modifications of transferrin and alendronate for bone and myeloma targeting. (21st November 2016) - Chang, Qing; Geng, Rui; Wang, Shanzheng; Qu, Ding; Kong, Xiangfei
Abstract: Treatment for multiple myeloma (MM) with a combined strategy of bone and tumor targeting remains a crucial technical challenge due to the incorporation of various functional components into one single system. Here, we developed dioleoyl phosphatidic acid (DOPA)-based paclitaxel (PTX)-loaded liposomes with modifications of alendronate and transferrin (Ald-/Tf-modified PTX-L), which were capable of bone affinity mediated by phosphate groups in DOPA and alendronate, and tumor targeting offered by transferrin. Ald-/Tf-modified PTX-L had clear and well-defined spherical shape with an intermediated size of 118.8 ± 4.8 nm, a highly negative surface charge of −46.9 ± 6.8 mV and a drug entrapment efficiency (DEE) of approximately 80%. When the pH was changed from pH 7.4 to pH 6.5, the accumulative release of PTX from Ald-/Tf-modified PTX-L significantly increased from 26.7 ± 3.7% to 41.7 ± 4.9%. Importantly, liposomes based on DOPA displayed an obviously stronger affinity with hydroxyapatite (HAp) than 1, 2-distearoyl-sn-glycero-3-phosphoethanolamine (DSPE)-based liposomes. Compared to PTX-L, Ald-/Tf-modified PTX-L exhibited obvious improvement of cytotoxicity (IC50  =  1.25 ± 0.09 μg/mL), significant enhancement on PTX intracellular accumulation (16.58 ± 0.62 μg/mg) and notable promotion to apoptosis induction (45.21 ± 3.10%) toward myeloma (MM1s) cells. In this study of antitumor efficacy, Ald-/Tf-modified PTX-L with bone-specific targeting showed a significant effect on extending the median survival time (48 days) and terminal survival time (> 58 days) against the MM1S-injected nude mice among all formulations. The results suggested that Ald-/Tf-modified PTX-L had potential as an efficient anticancer drug delivery system for MM therapy.